Juvenile Systemic Lupus Erythematosus and Glioblastoma: A Case Report and Literature Review - Mohammed A. Muzaffer, (Journal of King Abdulaziz University: Medical Sciences, 2023)
This is a case report of 11-years-old Chadian female, diagnosed with juvenile systemic lupus erythematosus based on five out of eleven criteria of the American College of Rheumatology. Her disease was under control on oral prednisolone, azathioprine and hydroxychloroquine. One year after diagnosis, she presented to the emergency department complaining of severe headache, vomiting and deterioration in the level of consciousness. Urgent brain computed tomography scan showed large brain tumour in the left parietooccipital region with significant midline shifting. Craniotomy and excisional biopsy of the mass was performed by a neurosurgeon. Histopathology reports a high grade malignant glioblastoma multiforme. Three cases were reported in the literature as space occupying lesion in the brain in juvenile systemic lupus erythematosus. To our knowledge, glioblastoma multiforme is the first case to report in juvenile systemic lupus erythematosus. Thus, severe headache and unusual neurological manifestations in juvenile systemic lupus erythematosus may be related to space occupying lesion, and should be evaluated immediately for early medical and surgical management.